Boosting ethanol electrooxidation via photothermal effect over palladium/reduced graphene oxide. Issue 38 (19th September 2018) - Wu, Yongmeng; Han, Shuhe; Huang, Yi; Shi, Yanmei; Zhang, Bin
Abstract : A photothermal effect strategy to combine the model thermal material, namely, reduced graphene oxide with active species (Pd) was developed to greatly improve the activity and stability of the alcohol electrooxidation reaction. Abstract : A photothermal effect strategy to combine the model thermal material, namely, reduced graphene oxide with active species (palladium) was developed to greatly improve the activity and stability of ethanol electrooxidation reaction (EOR). The improvement can be ascribed to both accelerated reaction kinetics of EOR and promoted desorption of the toxic reaction intermediate COads from active palladium caused by the efficient light absorption and subsequent conversion to thermy of reduced graphene oxide. Additionally, this photothermally enhanced strategy was found to be suitable for electrooxidation reactions of other alcohols ( e.g., ethylene glycol and glycerol).